Correlation Between Sleep Patterns and Blood Pressure in Students of Universitas Prima Indonesia - Yang, Jason; Bob Haykal, Teuku; Barus, Melvin Nova Gunawanto; Indharty, R. R. Suzy (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2024)
Introduction: Hypertension is a chronic condition which blood pressure increases above normal limits. It can cause a variety of other health issues such as heart, eyes, and kidney problems. Hypertension can occur due to various risk factors such as sleep disturbance. Sleep disturbance often occurs in students that could be affected by demands from college such as attending school community, school tasks, or exams. Objective: Correlation between sleep patterns and blood pressure in students of the Faculty of Medicine, Universitas Prima Indonesia in 2023. Method: Cross-sectional, the samples in this study are students of the Faculty of Medicine, Universitas Prima Indonesia, Class 2020-2022 who had met the selection and exclusion criteria based on the quota sampling technique. The data was then analyzed with the Chi-Square test. Result: The calculation results show that out of 85 respondents, 49 people (57,6%) had poor sleep patterns and 36 people (42,9%) had good sleep patterns. Out of 85 respondents, 11 people (12,9%) had normal blood pressure, 35 people (41,2%) had pre-hypertension blood pressure, 33 people (38,8%) had stage 1 hypertension blood pressure, and 6 people (7,1%) had stage 2 hypertension blood pressure. The Chi-Square test results showed no meaningful relationship between sleep patterns and blood pressure (p value=0,929). Conclusion: There is no meaningful relationship between sleep patterns and blood pressure of Universitas Prima Indonesia students in 2023. Keywords: blood pressure, hypertension, sleep patterns